LECTURER RESOURCE DEVELOPMENT DESIGN OF DARUNNAJAH UNIVERSITY JAKARTA FROM 2023 TO 2031 - Manaf, Sofwan; Ritonga, Matnur (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2024)
Three colleges—STII Darunnajah Jakarta, STAI Darunnajah Bogor, and STAI Darunnajah Jakarta—that were part of the Darunnajah Foundation gave birth to Darunnajah University. Following their 2022 merger to form Darunnajah University, the first thing to be mapped and designed is the Lecturer Resources. This is looking at the state of existing lecturers, and then the birth of five new study programs. This study used a case study methodology, employing a qualitative approach through observation, interviews, and documentation. Data were collected, reduced, presented, and conclusions drawn. The study's findings demonstrated Darunnajah University's seriousness in planning its teaching workforce for 2023–2031. Where the HR bureau is guided by the strategic plan and renovation; 1) Development of existing lecturers by encouraging them to continue their studies, providing scholarships, and providing recommendations for scholarships. 2) Cultivating the values of panca jiwa, panca bina, panca jangka, and panca dharma towards lecturers 3) Recruitment of linear lecturers. 4) Benchmarking good practices of HR development for lecturers to UNIDA Gontor. 5) Targeted in 2031, there are 13 professors.